دراسة بصرية لشاهد قبر أبي قاسم الزليجي بتونس، ت. 902 هـ. = 1496 م.: نشر جديد ودراسة مقارنة في قواعد المنظور - أبو شنب، السيد سعيد زكى (الإتحاد العام للآثاريين العرب, 2021)
تعد الدراسة البصرية من أهم الدراسات الحديثة في مجال الآثار سواء من الناحية المعمارية أو الفنية، كما أنها من أهم المجالات التي يجب الالتفات إليها، خاصة أن هذه الدراسة توضح لنا الكثير مما كان يهدف إليه الفنان أو المعماري وقت العمل المقصود، أما في مجال النقوش الكتابية فإن هذه الدراسة تهدف إلى الكشف عن الرسالة التي كان يريد كاتب النص إيصالها للمتلقي فانعكست بشكل مباشر على اختيار الشكل العام للنص ونوع المادة المكتوب عليها ونوع الخط المنفذ به النص قبل الدخول في تحليل العبارات والكلمات الواردة بالنص المطبق عليه هذه الدراسة. ويهدف هذا البحث في تطبيق الدراسة البصرية على شاهد قبر لأبي قاسم الزليجي (ت 902 ه/ 1496 م)، بالزاوية المسماه باسمه بمدينة تونس (ينشر لأول مرة)، وذلك بتحليل هذا الشاهد من حيث الشكل والمضمون، لاستخراج عوامل الجذب البصري التي عمد لها الكاتب لجذب المتلقي لقراءة النص والتعرف على الرسالة المقصودة منه التي ارادها المرسل، كما يعد تحليل نص هذا الشاهد من الأهمية بمكان لأن هذا تاريخ كتابته في وقت لاحق لوفاة أبي قاسم الزليجي، فكان اختيار بعض الألفاظ يعطينا الكثير من المعلومات عن شخص أبي قاسم الزليجي كما تنقل لنا الكثير من المعطيات عن طبيعة الفترة التالية لوفاته، وطبيعة المقيمين في هذا المكان في فترته وحتى بعد وفاته. لذلك كان اختيار موضوع البحث "" دراسة بصرية لشاهد قبر أبي قاسم الزليجي بتونس (ت 902 ه/ 1496 م) نشر ودراسة في قواعد المنظور"" موضوعا لهذا البحث."
The visual study is one of the most important modern studies in the field of archeology, whether from an architectural or even a technical point of view, and it is also one of the most important areas that must be paid attention to, especially since this study displaces much of what the artist or architect was aiming for, but in the field of inscriptions This study aims to reveal what the author of the text was aiming for in terms of choosing the general form of the text, the type of material written on it, and the type of font in which the text was executed before entering into the analysis of the expressions and words contained in the text to which this study is applied. This peaper aims to apply this study to a tombstone of Abu Qasim Al-Zilaiji in the cemetery named after him in the city of Tunis by (It is published for the first time) analyzing this witness in terms of form and content and comparing it with a number of evidence from the same cemetery, which is close in the date of writing in the same period of time and takes the same shape and executed with the same type of script Al-Mukhtar, and the analysis of the text of this witness is of great importance because this is the date of its writing at a later time of the death of Abu Qasim al-Zulaiji, so choosing some words gave us a lot of information about the person of Abu Qasim al-Zulayji, as well as a lot of data about the nature of the period and the nature of the residents of this place. In his period and even after his death. Therefore, the selection of the research topic was ""a visual study of the tombstone of Abu Qasim Al-Zilaiji in Tunis (d. 902 AH / 1496 AD, published and a comparative study in the rules of perspective"" for a group of the evidence in that cemetery."
Keywords: المؤثرات البصرية -- الموروث الحضاري -- العمارة التونسية -- المقابر الجنائزية